KUALITAS INFORMASI AKUNTANSI SEKTOR INDUSTRI SEBELUM DAN SELAMA PANDEMI COVID-19: STUDI NEGARA-NEGARA ASEAN - Slamet Sugiri; Retno Yuni Nur Susilowati (Faculty of Economics and Business, 2021)
The purpose of this paper is to examine the effect of the Covid-19 pandemic on the quality of accounting information in terms of accrual quality and value relevance. This study uses a sample of companies listed on stock exchanges in five ASEAN countries, Indonesia, Malaysia, the Philippines, Singapore, and Thailand, for the period 2009-2020. OLS pooled regression model was estimated with panel data. The results showed that the COVID-19 pandemic impacted earnings quality, but not on value relevance of accounting information quality. Enforcement of accounting and auditing standards can reduce the impact of the COVID-19 pandemic in improving earnings quality. However, investor protection is not adequate to improve the quality of accounting information during the COVID-19 pandemic.